Effects of different types and concentration of hydrocolloids on mango filling - Razak, R. A.; Karim, R.; Sulaiman, R.; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Hydrocolloid has long been utilized as a thickener to increase the consistency such as fruit jam. In this study, the optimum type (xanthan gum/XG, Arabic gum/AG, guar gum/GG, locust bean gum/LBG, pectin/ PC and carboxymethylcellulose/ CMC) and concentrations (0.2%, 0.4%, 0.6%, 0.8%, and 1% (w/v)) of the hydrocolloid as thickening agents in ‘Chok Anan’ mango filling was determined using Full Factorial design (108 trials). Physicochemical analyses, including total soluble solid (TSS), pH (acidity), moisture content, and viscosity (Power Law) were conducted. The predicted values for 1.0% PC, and 0.2% XG with the response as TSS (44.9ºBrix), acidity (3.4), moisture content (47.48%) and pseudoplastic behavior (shear thinning) value of n = 0.2917 were similar to experimental optimum values. The optimum type (PC) and concentration of hydrocolloids (1%) of experimental values (TSS= 45.3ºBrix, pH= 3.41) show insignificant different with predicted values. The concentrations (0.2%, 0.4%, 0.6%, 0.8% and 1.0%) and type of the hydrocolloids (XG, AG, GG, LBG, PC and CMC applied in this study had significantly (p<0.05) affected the acidity value, TSS, moisture content, and flow behavior index of mango filling. The mango fillings with PC as hydrocolloid may diversify the application of local mango fruits.